Structural Effects on the Acid-Catalyzed Hydrolysis of (E)-3-Carboxy-4-Aryl-But-3-Enoic Anhydrides - M. Abdallah, Shadia (Asian Journal of Chemistry, 2010)
The rates of acid-catalyzed hydrolysis of (E)-3-carboxy-4-phenyl (1), 4-(1-naphthyl) (2) 4,4-diphenyl(3) and 4-methyl, 4-phenyl(4)-but-3-enoicanhydrides are compared in dioxane-water mixture at different temperatures and pH values and are in the sequence 1 > 2 > 3 > 4. The rate decreases with increase of pH, reaches a minimum at about pH 3.1 then increases gradually till pH 5.7.